From Scratch - Kafejian, Sergio (Revista Vórtex, 2020)
Written in 2017 for acoustic guitar and electronics From Scratch reflects several years of my research upon the classical guitar sound’s possibilities. The sonorities used came out from exploring the instrument in different musical contexts and languages as free improvisation, jazz, Brazilian popular music and classical concert music . From Scratch’s main proposal is to integrate the vast sound range obtained by exploring traditional technics, extended technics, live processing and fixed media resources.